(3GdJVNe h GdcSGOs - (3MSjf Hf SGde LGHQ(B, (3GdRHjOjs ((3YeGf(B:s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B,s, 2011)
(3eaghe GdJVNe h GdcSGO h bjGSg, GdeDSSI GdfbOjI h OhQgG aj GdMO ef GdJVNe h GdcSGO, deMI Yf CSHGH GdJVNe h GdcSGO ef GdfGMjI GdNGQLjI h ef GdfGMjI GdYdejI hGdYGeI h gPg GdGNjQI JfGhdJ GdghS GdGSJgdGcj h eTcdI GdJVNe, GdGMJcGQh GdHWGdI h eTcdI GdJVNe h GdcSGO h fJGFL GdJVNe h GdcSGO, GLQGAGJ h Mdhd hbGFjI ef CNWGQ GdJVNe h GdcSGOs
(3HHdjhZQGajG(B: (3U(B.463-477s
Keywords: (3GdCReGJ GdEbJUGOjIs; (3GdJVNe GdeGdjs; (3GdcSGO GdEbJUGOjs